Further Investigation on the Flow and Heat Transfer Mechanism of Single-Jet Film Cooling Based on Hybrid Thermal Lattice Boltzmann Method (Communications in Computational Physics, 2020)
Massively parallel simulation applied multiple graphic processing units(multi-GPUs) is carried out to perform an in-depth investigation on the flow and heattransfer mechanism in film cooling based on hybrid thermal lattice Boltzmann method(HTLBM). For the flow field, multiple-relaxation-time (MRT) collision model is used.A coolant jet is injected at an inclined angle of α=30◦into a turbulent flat plate boundarylayer profile with free-stream Reynolds number of Re = 4000. In our previouswork [1], we proposed a three-part definition for the jet-crossflow-interaction regionaccording to the turbulent kinetic energy (TKE) distribution and the unsteady mixingcharacteristics in each domain were studied qualitatively. In order to further investigatethis phenomenon, a more detailed study on unsteady flow and heat transfercharacteristics is performed in this work. The results show that the shear domain isdominated by the shearing effect and covered by stable coolant film. In rotating domain,the turbulent intensity increases because of the violent mixing between crossflowand jet flow and the coolant film begins to spread in lateral. All of these causethe rapid decrease in coolant film stability. The great turbulent-dissipation effect indissipation domain weakens the turbulent intensity and strengthens the fluctuation ofspanwise velocity. The cooling performance is very poor.
Keywords: Hybrid thermal lattice Boltzmann method; multiple-relaxation-time collision model; multiple graphic processing units; film cooling; mixing mechanism.